Off-line signature verification using backpropagation technique - Porle, A.R (University Malaysia Sarawak, UNIMAS., 2004)
An automated off-line signature verification is becoming an important technology due to most of the financial transaction and documents approval are still being carried out using a paper. This final year project presents a research for developing and designing an off-line signature verification system. Three important stages to develop and design the system are the pre-processing, feature extraction and artificial neural networks.